Aurora: a mobile-based cognitive behavioral therapy intervention for anxiety and depression in Mexico - López-Tello, Alejandro; Pérez-Gómez, Adriana; Toledo-Lozano, Christian Gabriel; Callejas-Gómez, María del Pilar; Durón-Figueroa, Raúl; Moreno-Coutiño, Ana; Ramirez-Treviño, Antonio; Nava, Sebastián; Ocampo-Gutiérrez de Velasco, Diego Antonio; Zárate, Edith; Arias-Carrión, Oscar (Frontiers in Psychology, 2025)
BackgroundAnxiety and depression are leading contributors to disability worldwide. In Mexico, an upper-middle-income country (UMIC) with health-system constraints resembling those of low- and middle-income countries (LMICs), access to psychotherapy remains limited. Digital therapeutics provide a scalable approach to bridging this gap. Aurora is a Spanish-language, self-guided mobile application delivering cognitive behavioral therapy (CBT) through eight interactive modules. This study evaluated its feasibility, usability, and preliminary clinical impact among pharmacologically treated adults with anxiety and depression.MethodsWe conducted a mixed-methods, pre–post feasibility study in Mexico between March and October 2024. Participants were 46 adults (18–45 years) with psychiatrist-confirmed mild-to-moderate anxiety and/or depression on stable pharmacotherapy; 38 (82.6%) completed baseline and follow-up. Usability was assessed with the System Usability Scale (SUS) and the user Mobile App Rating Scale (uMARS). Symptoms were measured with the Spanish Goldberg Anxiety and Depression Scale (GADS). The number of modules completed defined engagement, categorized as follows: low (0–2), moderate (3–5), and high (6–7). Analyses included paired t-tests, non-parametric trend tests, correlations, and adjusted regressions.ResultsAnxiety scores decreased from 13.2 (SD 5.6) to 10.6 (SD 5.1) (t(37) = 3.81, p = 0.001; d = 0.49), and depression scores from 11.1 (SD 5.2) to 8.4 (SD 4.9) (t(37) = 4.75, p < 0.001; d = 0.54). Engagement showed a graded dose–response: high-engagement users (n = 17) achieved larger reductions (Δ anxiety = −3.9; Δ depression = −4.0) than low-engagement users (Δ anxiety = −0.9; Δ depression = −1.0). Regression confirmed each additional module predicted incremental reductions in both anxiety (β = −0.38, p = 0.009) and depression (β = −0.41, p = 0.006). Usability ratings were high (SUS = 78.5/100; uMARS = 4.2/5).ConclusionAurora was feasible, usable, and associated with moderate symptom reduction in pharmacologically treated patients. The observed dose–response underscores the clinical importance of sustained engagement. These findings highlight the potential of co-designed, culturally tailored digital therapeutics to expand access to mental health care in Spanish-speaking UMIC and LMIC settings, warranting confirmation in larger controlled trials.